Reliability and Validity Test Of Indonesian Version Short Form12 Quality of Life Questionnaire in Rheumatoid Arthritis Patient - Falah, Nabil Mubtadi; Putranto, Rudi; Setyohadi, Bambang (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Rheumatoid Arthritis is a chronic disease requiring a long-term medication affecting quality of life. Short Form 12 is a generic questionnaire to assess patients quality of life and has been validated in England. This study was designed to test reliability and validity of Indonesian version of SF-12 questionnaire. Methods. Sixty-five patients with clinically diagnosed RA using ACR/EULAR criterion were interviewed using Short Form 36 and Short Form 12 questionnaire. Validity was assessed with construct validity and external validity, while reliability tested with internal consistency and test-retest method. Results. Short-Form 12 (Indonesian Version) did not proved having a good validity, as it have a poor correlation between RE and MH domain in SF-36 and SF-12. Indonesian version of SF-12 shown a poor internal consistency (Cronbach Alpha: 0.561- 0.754) but a good test and retest reliability ( intraclass correlation coefficient: 0.844-0.980, p <0,05) Conclusions. Indonesian version SF-12 is not reliable nor valid to evaluate quality of life in RA patients.